Bioinspired Chromotropic Ionic Skin with In‐Plane Strain/Temperature/Pressure Multimodal Sensing and Ultrahigh Stimuli Discriminability. (17th September 2022) - Zhang, Heng; Chen, Haomin; Lee, Jeng‐Hun; Kim, Eunyoung; Chan, Kit‐Ying; Venkatesan, Harun; Adegun, Miracle Hope; Agbabiaka, Okikiola Ganiu; Shen, Xi; Zheng, Qingbin; Yang, Jinglei; Kim, Jang‐Kyo
Abstract: Electronic skins (e‐skins) mimic multimodal sensing capabilities of various tactile receptors in natural skin. Herein, a stretchable chromotropic ionic skin is rationally designed to simultaneously detect and decouple multiple stimuli, including in‐plane strain, temperature, and pressure. The mutually discriminating trimodal ionic skin consists of mechanochromic, thermoresistive and triboelectric layers that individually function as strain, temperature and pressure sensors, respectively. These three distinct capabilities are integrated into the ionic skin which demonstrates highly sensitive responses to selective external stimuli while upholding high insensitivity to unwanted ones. The structural colors derived from mechanochromic photonic crystals of magnetic ferroferric oxide‐carbon nanoparticles respond to strains by color‐switching in the full visible spectrum, exhibiting appealing potential in interactive stress visualization. The temperature detection with an exceptional sensitivity of 20.44% per °C is enabled by the thermoresistive effect of ionic hydrogel, while oriented polymer chains embedded in the hydrogel decouple temperature from extraneous stimuli. The multilayer structure consisting of an ionic hydrogel film, a wrinkle‐patterned polydimethylsiloxane (PDMS) film with gradient modulus design and a carbon nanotubes/PDMS electrode displays an extraordinary triboelectric effect with a strain‐ and temperature‐insensitive pressure sensing capability. The chromotropic ionic skin facilitates simultaneously accurate measurements, high discriminability and quantitative mapping of complex stimuli, offering new insights into emerging E‐skins. Abstract : A mutually‐discriminating trimodal ionic skin is designed to simultaneously detect and decouple in‐plane strain, temperature, and pressure stimuli by means of multiple sensing principles of the mechanochromic, thermoresistive, and triboelectric effects. These three distinct capabilities manifest a highly sensitive response to a selective external stimulus while upholding high insensitivity to extraneous ones.